RACIAL PROFILING ON POLICE STOP AND SEARCH PRACTICE AS PORTRAYED IN THE GEORGE TILLMAN’S MOVIE THE HATE U GIVE - Dea Via Ranti; Ely Nurmaily (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2021)
Racial profiling becomes public spotlight over the past two decades in America that creates right devastation and discrimination. Therefore, this thesis aims to find racial profiling on police stop and search as portrayed in the movie The Hate U Give by Goerge Tillman which the movie tells about the life of Afro-American people who lived discriminated by state institutions. The objectives of this study are to describe the potrayal of racial profiling in Angie Thomas The Hate U Give movie and to find the motive of Racial profiling in Angie Thomas The Hate U Give movie. This study is typical library research with descriptive qualitative method. This study used critical race theory by Delgado and Stefancic (2001), racial profiling theory by Filimon (2015), and also movie theory by Boggs and Petrie. At the end of this study, the writer finds that the racial profiling practice in the movie is portrayed through events and experiences in the form of discrimination in police service and bias in news media. Meanwhile, the motives of racial profiling are police strategy specifically enforcement, prejudice and law bias.